2021
DOI: 10.34140/bjbv3n1-018
|View full text |Cite
|
Sign up to set email alerts
|

Impacto de los programas de becas en la movilidad de estudiantes internacionales: el caso de Brasil / Impacto dos programas de bolsas de estudos na mobilidade de estudantes internacionais: o caso do Brasil

Abstract: Impacto de los programas de becas en la movilidad de estudiantes internacionales: el caso de Brasil Impacto dos programas de bolsas de estudos na mobilidade de estudantes internacionais: o caso do Brasil

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 12 publications
0
0
0
Order By: Relevance
“…Research has shown how the historical link between countries, a colonial past, or a common language [13][14][15][16][17][18][19], a deficit in training provision or the perception of the quality of training in home countries [20][21][22][23][24][25], as well as the prestige and/or reputation of host institutions [13,[26][27][28][29][30] often wrongly represented by international rankings, encourage (or maybe promote) mobility flows and the choice of certain destinations when pursuing a degree abroad.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Research has shown how the historical link between countries, a colonial past, or a common language [13][14][15][16][17][18][19], a deficit in training provision or the perception of the quality of training in home countries [20][21][22][23][24][25], as well as the prestige and/or reputation of host institutions [13,[26][27][28][29][30] often wrongly represented by international rankings, encourage (or maybe promote) mobility flows and the choice of certain destinations when pursuing a degree abroad.…”
Section: Introductionmentioning
confidence: 99%
“…The scale of this phenomenon attests to the importance of research in the field, which has been prominent on the agendas of higher education institutions for more than two decades. The lack of studies on the transition to Master's degrees and on the specific group of international students in the Spanish context [16,[31][32][33][34] makes this study necessary in complementing an already extensive body of research carried out in other countries.…”
Section: Introductionmentioning
confidence: 99%